Prove using natural deduction rules, give a formal proof (1)(P v R) -> (Q v s) from the premise Q -> Q, R -> S

(2) (~P v Q) -> (P->Q)

(2) (~P v Q) -> (P->Q)

### Recently Asked Questions

- Hi I'm not sure what I'm supposed to differently in this question. How does them being mutually exclusive change the question? Suppose A, B and C are 3 events

- how to do the second question？ I try to start it, but I have no idea to solve it, can you tell me what is the next step?

- the height h of a ball t seconds after it is thrown upward from a height of 6 feet and with an initial velocity of 48 feet per second is h(t) = -16t^2 + 48t +